A novel GaN-based lateral SBD with a TUG-AlGaN/GaN heterojunction. (February 2019) - Shi, Yijun; Chen, Wanjun; Wu, Shan; Liu, Chao; Xia, Yun; Li, Maolin; Cui, Xingtao; Chen, Tangsheng; Zhou, Qi; Deng, Xiaochuan; Zhang, Bo
Abstract: In this study, a novel GaN-based lateral Schottky barrier diode (SBD) with a thin upward graded AlGaN (TUG-AlGaN) barrier layer is proposed and investigated. The TUG-AlGaN layer upward graded from 0 to 0.50 mol fraction is used to replace the thick AlGaN layer of the heterojunction, which can reduce the distance from the 2-D electron gas (2DEG) to the Anode electrode, retain high density of 2DEG near the heterojunction, and eliminate the abrupt AlGaN/GaN conduction band offset at same time, subsequently can reduce the turn-on voltage and on-state voltage. The simulated results show that compared with the conventional SBD (with 25 nm Al0.23 Ga0.77 N layer), the proposed SBD achieves 0.32 V reduction in turn-on voltage, and 1.21 V reduction in on-state voltage. Meanwhile, although the proposed SBD doesn't deliver obvious improvement in static characteristics when compared with the GaN-Based lateral field-effect rectifier (L-FER) (with 25 nm Al0.23 Ga0.77 N layer), the reverse recovery time of the proposed SBD is much smaller than that of the L-FER (with 25 nm Al0.23 Ga0.77 N layer). The outstanding static characteristics combined with excellent switching characteristics reveal its great potential for future power applications. Highlights: A novel GaN-based lateral SBD with a TUG-AlGaN/GaN heterojunction is proposed. The proposed SBD exhibits a low turn-on voltage of 0.6 V. The reverse recovery time of the proposed SBD is much smaller than that of the L-FER.